The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1209/epl/i2005-10072-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear terms in 2D cosmology

Abstract: Abstract. -In this work we investigate the behavior of two-dimensional (2D) cosmological models, starting with the Jackiw-Teitelboim (JT) theory of gravitation. A geometrical term, non-linear in the scalar curvature R, is added to the JT dynamics to test if it could play the role of dark energy in a 2D expanding universe. This formulation makes possible, first, the description of an early (inflationary) 2D universe, when the van der Waals (vdW) equation of state is used to construct the energymomentum tensor o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This is also the case to describe the transition to a final period (leaving the matter dominated era) when the non-linear term in R starts to show its effects and promotes the desired accelerated regime, that would correspond to the dark energy dominated era. The results have also shown that the role of the non-linear term is similar to the one found in 2D (when it is used the JT model [7]); although this parallel can be done only qualitatively: different forms in the explicit expressions for the dynamics are found and also different values of parameters are necessary to select the more interesting scenarios. In both cases the analysis and results remain as theoretical explorations of hypothetical universes in lower dimensions.…”
Section: +H; 9880 -Kmentioning
confidence: 70%
See 3 more Smart Citations
“…This is also the case to describe the transition to a final period (leaving the matter dominated era) when the non-linear term in R starts to show its effects and promotes the desired accelerated regime, that would correspond to the dark energy dominated era. The results have also shown that the role of the non-linear term is similar to the one found in 2D (when it is used the JT model [7]); although this parallel can be done only qualitatively: different forms in the explicit expressions for the dynamics are found and also different values of parameters are necessary to select the more interesting scenarios. In both cases the analysis and results remain as theoretical explorations of hypothetical universes in lower dimensions.…”
Section: +H; 9880 -Kmentioning
confidence: 70%
“…These ideas come in substitution to the standard formulations that take the dark energy as a "usual" source [6]. This approach was tested in a 2D context recently by these authors [7], working with the Jackiw-Teitelboim (JT) model [1,9].…”
Section: +H; 9880 -Kmentioning
confidence: 99%
See 2 more Smart Citations